1996
DOI: 10.3810/psm.1996.10.1327
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Managing Concussion in Sports

Abstract: In their approach to managing athletes who sustain concussions, sports physicians differ at least as widely as do the many published guidelines on the subject. The scarcity of scientific evidence makes practical decisions about when an athlete can safely return to the field difficult. Efforts to forge a consensus are underway, but controversy persists around such questions as whether a brief loss of consciousness should be classified as a severe concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…7 One would expect that sports medicine physicians would be in better compliance with return to play guidelines, but a survey of members of the American Society for Sports Medicine found that only 30% of sports medicine physicians treated concussions per established guidelines. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 One would expect that sports medicine physicians would be in better compliance with return to play guidelines, but a survey of members of the American Society for Sports Medicine found that only 30% of sports medicine physicians treated concussions per established guidelines. 8…”
Section: Introductionmentioning
confidence: 99%
“…Continued controversy surrounds the use of classification scales used for MTBI sustained in sports [25]. Numerous scales have been published, and each differs considerably in its criterion for rating the severity of a head injury as well as return-to-play guidelines [26]. Yet, in each case, these classification scales lack appropriate scientific support [27].…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42][43] In an attempt to standardize the definition and other aspects of sport-related concussion assessment and management, there have been several international conferences on concussion in sport, the last of which occurred in Zurich in 2012, [44][45][46][47] which defines concussion as follows: [38][39][40][41][42][43] In an attempt to standardize the definition and other aspects of sport-related concussion assessment and management, there have been several international conferences on concussion in sport, the last of which occurred in Zurich in 2012, [44][45][46][47] which defines concussion as follows:…”
Section: Definition Biomechanics and Pathophysiologymentioning
confidence: 99%